Effect of pretreatment on the nutritional quality of Agaricus bisporous - RANJANA ACHARYA; Anuradha Dutta; Archana Kushwaha; S.K. Mishra; Anil Kumar; U.C. Lohani; G.S. Kushwaha (Mushroom Research, 2023)
Mushroom is considered a superfood because of their diverse nutrient content. The growing production of mushrooms has been seen due to its increased per capita consumption. Drying is one of the oldest methods to preserve food. In this study, the Agaricus bisporous mushroom was dried after given pretreatment to them in three different ways and the effect of these pretreatments on the color, percent recovery, and nutritional composition of the aforementioned mushroom was studied. The study concluded that the percent recovery after drying decreases in treated mushrooms compared to the non-treated. The color of the treated is more appreciable than the non-treated counterpart. Pretreating the mushroom before drying had a significant effect on the moisture, protein, and carbohydrate content.